Magnetic resonance imaging of the regenerating neonatal mouse heart - Gunadasa-Rohling, M; Masters, M; Maguire, M; Smart, S; Schneider, J; Riley, P (American Heart Association, 2018)
After myocardial infarction (MI) the human heart is unable to regenerate lost tissue, leading to scarring, pathological remodeling and progression to heart failure. The study of animal models that can intrinsically regenerate their heart, therefore, offers therapeutic insight into targeting tissue restoration. In 2011, the first evidence of mammalian heart regeneration was reported by Hesham Sadek, Eric Olson and colleagues1. Following surgical resection of ~15% of the left ventricle apex of a oneday old (P1) neonatal mouse, the heart fully regenerated by 21-days post-injury, whereas if the procedure was repeated one week later on a post-natal day 7 (P7) mouse heart, fibrosis and scarring ensued, recapitulating the adult wound-healing response. The mechanism of regeneration observed involved proliferation of resident cardiomyocytes, analogous to that described in the adult zebrafish heart2. Since the original study others have described neonatal myocardial regeneration after alternative insults, such as MI3. However, there is also controversy surrounding the extent of heart regeneration during the first weeks of life, whereby it was reported regeneration did not occur in the P1 heart and was replaced by long-term fibrosis (180 days) with extensive cardiac remodelling4.